2019
DOI: 10.7567/1347-4065/ab14fb
|View full text |Cite
|
Sign up to set email alerts
|

Diameter dependence of single-walled carbon nanotubes with flavin adenine dinucleotide glucose dehydrogenase for direct electron transfer bioanodes

Abstract: The diameter dependence of single-walled carbon nanotubes (SWCNTs) with flavin adenine dinucleotide glucose dehydrogenase (FAD-GDH) for direct electron transfer (DET) type bioanodes is presented for the first time. In order to address the issue, we use SWCNTs having different diameters fabricated by direct-injection pyrolytic synthesis, which can control the diameter in a wide range with the other parameters fixed. Three different diameters of SWCNTs are examined: average diameter d m = 1.0, 1.5, and 2.0 nm. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A previous work examining direct electron-transfer bioanodes using CNTs with flavin adenine dinucleotide-dependent glucose dehydrogenase (FAD-GDH) suggested that a CNT is inserted into the groove of FAD-GDH . In fact, the groove of FAD-GDH was found to show relatively high aromaphilicity (Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous work examining direct electron-transfer bioanodes using CNTs with flavin adenine dinucleotide-dependent glucose dehydrogenase (FAD-GDH) suggested that a CNT is inserted into the groove of FAD-GDH . In fact, the groove of FAD-GDH was found to show relatively high aromaphilicity (Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…A previous work examining direct electron-transfer bioanodes using CNTs with flavin adenine dinucleotide-dependent glucose dehydrogenase (FAD-GDH) suggested that a CNT is inserted into the groove of FAD-GDH. 68 In fact, the groove of FAD-GDH was found to show relatively high aromaphilicity (Supporting Information, Figure S4). A future challenge using the aromaphilicity index is to control the protein binding affinity for aromatic carbon surfaces, including that of nanomaterials and solutes, by designing aromaphilicity profiles of protein surfaces using point mutations, which can contribute to a wide range of protein applications, such as bioimaging, biomedicine, biosensing, and drug delivery.…”
Section: ■ Methodsmentioning
confidence: 99%
“…17,18) Moreover, owing to their unique dimensions, SWNTs can closely approach the active centers of enzymes, thus possibly making direct electron transfer (DET) via the tunneling process more feasible. 19) Hence, SWNT thin films are optimal candidates for the DET electrodes of flexible EBFCs for realizing selfpowered wearable sensors.…”
mentioning
confidence: 99%
“…The enzymes glucose oxidase (GOx) from Aspergillus niger (Tokyo Chemical Industry) and horseradish peroxidase (HRP) (Sigma-Aldrich) were used at the anode, while laccase from Trametes versicolor (Sigma-Aldrich) was used at the cathode. The enzymes facilitate highly specific catalysis and the electrons may be easily transferred to the SWNTs owing to their close contact with the active centers of the enzymes, 19) as illustrated in Fig. 1(b).…”
mentioning
confidence: 99%